(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
For many organizations, keeping data private and secure has also become a compliance requirement. Cloud providers offering Infrastructure as a Service (IaaS) and Platform as a Service (PaaS) offer a â€œshared responsibilityâ€ model for customer applications and data, so companies that are migrating to the cloud are responsible for finding a solution. This research paper proposes a system, which combines encryption with key management to protect critical data in public, private and hybrid cloud environments.